(3fgGjI GdCed aj TQM GdLed ddNhfLis - (3eMeO Hf CMeO Hf eMeO Hf eQRhb GdJdeSGfis; (3GdNhfLj , eMeO Hf fGeGhQ Hf YHO Gdedc, GaVd GdOjf CHh YHO Gddg,J (B646 (3g` s
(3ChdgG (B:s
(3CeG HYO aUd Ydi GdefWb s
(3BNQgG (B:s
(3hSGdH GdMbjbI Ybje hgPG BNQ eG bUOfGg ef TQM cJGH GdLed s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B122 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B73s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1986s
Keywords: (3GdadSaI hGdefWbs